The Guys - Jim Simpson; La Paglia, Anthony; Charlotte Simpson; Irene Walsh; Jim Simpson; Julian Trompeter; Katharine Schreiber; Sigourney Weaver (USA ContentFilm, 2002)
Adapted from a stage play by Anne Nelson, a drama centering on a slice of the aftermath of the 9/11 tragedy. Nick, a fire captain, who lost eight men in the collapse of the World Trade Center, enlists help from an editor, Joan, to prepare their eulogies. Nick builds a relationship with Joan, who helps him put together the difficult, heartfelt speeches that he must deliver with honor, humor and poise--all the while, navigating his way through his own emotional response.
The story of a fire captain who lost eight men in the collapse of the World Trade Center and the editor who helps him prepare the eulogies he must deliver.
Anne Nelson
Languages: English, Turkish
Subtitles: English, Turkish
Keywords: Drama